Effectiveness of interventions for adherence to antiretroviral therapy in adults with HIV: a systematic review - Zuge, Samuel Spiegelberg; Paula, Cristiane Cardoso de; Padoin, Stela Maris de Mello (Revista da Escola de Enfermagem da USP, 2020)
Objective To identify the best available evidence of intervention effectiveness for adherence to antiretroviral therapy for HIV in adults. Method The methodology proposed by the Cochrane Collaboration was used, with search in the databases: PubMed, Embase, LILACS, CINAHL, Web of Science and SCOPUS. Randomized clinical trials of interventions to promote adherence to antiretroviral therapy for HIV, in the ≥ 18-year-old population, published from 2010 onward, were considered. The eligibility, inclusion and extraction of results were developed by two independent researchers. Results The five studies included in the quantitative analysis were effective interventions that developed educational actions with the patient, especially mediated by software, the use of medication schedule reminders and the inclusion of treatment supporters that also received educational actions to develop such role. Conclusion The combination of interventions strengthens the promotion of adherence. There is a need for investment in the implementation of educational actions with patients, such as the inclusion of supporters, in addition to counseling and electronic devices for reminders, which must be offered in the services in an articulated and continuous manner.